Developing competency to manage diversity : readings, cases & activities - Cox, Taylor, Jr., 1949-; Beale, Ruby L., 1949- (San Francisco : Berrett-Koehler Publishers ; Emeryville, CA : Publishers Group West [distributor], 1997)
Develop a critical competency for today's organizations - the ability to successfully manage diversity. Builds on the author's acclaimed volume, Cultural Diversity in Organizations; organizes learning and skill-building for diversity around thirty-one activities that can change behavior; addresses a wide range of diversity issues through twenty-three timely readings; integrates ideas from the academic world with real-life experience in six detailed case studies; and provides managers with tools they need to successfully managed a diverse workforce.
A framework for understanding competency for managing diversity -- Foundations for competency. The meaning of diversity -- Managing diversity as a business strategy -- Developing individual competency. Understanding group identities -- Stereotyping -- Prejudice and discrimination -- Cultural differences -- Developing organizational competency. Organizational culture -- Formal and informal structure of organizations -- A process for organizational change -- The continuing quest for excellence.
Includes bibliographical references (pages 333-345) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Diversity in the workplace; Cultural pluralism; Cultural Diversity; Multiculturalisme en milieu de travail; Diversité culturelle; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Diversity in the workplace; Diversity in the workplace; Organisatiecultuur; Personeelsmanagement; Gelijke behandeling; Diversity in the workplace